Long-term results of anti-VEGF therapy in macular edema caused by central retinal vein occlusion - A. B. Galimova; V. U. Galimova (Российский офтальмологический журнал)
Purpose. To evaluate long-term results of anti-VEGF therapy performed in a modified “treat-and-extend” regimen in macular edema secondary to central retinal vein occlusion.Material and methods. The prospective study included 29 patients (16 men and 13 women) aged 24–81. The median follow-up period was 36 months [24; 60]. 20 patients underwent ranibizumab monotherapy, 3 patients – aflibercept monotherapy, while 6 patients received a combination of the two drugs following the modified regimen, which allowed terminating anti-VEGF treatment when macular edema remission was achieved.Results. Macular edema completely resolved in 27 out of 29 patients (93.1%) by the end of the second year, while the remaining 2 patients showed the complete resolution during the third year. 18 patients (62.1%) could terminate anti-VEGF therapy during the first 6 months, whereupon they received 3 to 5 monthly injections with no macular edema relapse over the subsequent 21–22 months of the follow-up. 11 patients continued anti-VEGF therapy and averagely received 7.09 ± 1.14, 5.09 ± 2.34 and 2.18 ± 2.36 injections with individually determined intervals at years 1, 2 and 3, respectively. On the whole, 22 patients (75.9%) terminated anti-VEGF therapy and transferred to drugless observation at the end of year 2, while 5 other patients (17.2%) terminated anti-VEGF therapy during year 3. As a result of the treatment, the maximum BCVA improved from 0.15 [0.07; 0.3] to 0.7 [0.4; 0.9] by the end of year 1 (Z = -4.69; p = 0.0000027) and remained stable during the rest of the follow-up.Conclusion. Anti-VEGF therapy in modified treat-and-extend regimen is effective in macular edema secondary to central retinal vein occlusion. and results in a significant and sustainable visual acuity gain and complete resolution of macular edema with a minimum quantity of injections in most patients.